УМУМТАЪЛИМ ФАНЛАРИНИ ТАДБИРКОРЛИККА ЙЎНАЛТИРИБ ЎҚИТИШ ТИЗИМИНИ ТАКОМИЛЛАШТИРИШ - Мирзакаримова, М.М. (SCIENCE and SOCIETY, 2020)
The article outlines the pedagogical conditions for the teaching of general education to entrepreneurship, substantiation of theoretical and practical aspects and development of scientifically based proposals and practical recommendations, the process of teaching general education subjects in grades 10-11, focused on entrepreneurship, the content of teaching general education to entrepreneurship and opinions and considerations related to pedagogical conditions.